Estudo acerca da aplicação da lei Maria da Penha em contexto de interculturalidade: violência de gênero e cultura indígena em Pernambuco. - Silva, Glebson Weslley Bezerra da (2019)
This work seeks to understand the situations of domestic violence that indigenous women have faced in their interpersonal relations and to understand how the Brazilian legal system behaves in the face of these suffered violence. We understand the confrontation of gender violence as the criminalization of violence against women, not only by the letter of norms or laws, but also by the consolidation of cultural, social and political structures that are intimately linked to a patriarchal society. Thus, when considering the legal system a law with a woman's name, we observe the Maria da Penha Law as a legislative mechanism and as a way of preventing and curbing domestic violence against women. As for women being indigenous and in situations of domestic violence, we must take into account the cultural conception of gender and its resolutions of conflict. Thus, the present research aims to analyze the applicability of this norm in contexts of interculturality, universes of indigenous communities of the state of Pernambuco, to investigate the applicability and effectiveness of the norm from these cultural markers, thus choosing the Criminal Court located in the municipality of Pesqueira. It is justified since, when Law 11,340 / 2006 was approved, situations of violence against indigenous women in the context of the communities or outside them by men of the same ethnic group were not thought of. The specific objectives are to discuss the structures of power which are part of the colonial management model, as well as the discussion about how the feminine was built in the Criminal Justice System. Thus, we can understand how the indigenous female population is considered (and is considered) by the Criminal Justice System and how the power structures influence the invisibility and culture of the silencing and cover-up of the other, thus provoking a cultural genocide.